Development of Scoring System for Prediction of Choledocholithiasis - Legiran; Danny Amos Tarigan; Hafid Komar (Sriwijaya Journal of Surgery, 2018)
Introduction. Gallstones (cholelithiasis) and gallbladder stones (choledocholithiasis) are still a public health problem because of the high incidence rate. Management of stones in common bile duct (CBD) is done with history taking about patient complaints and tracking patient history such as yellow appearance, physical examination, laboratory examination, and imaging examination before, during and after surgery. Of the many imaging assessment that can be done, in practice not all can be done because these tests are expensive, complicated, risk of morbidity and mortality. A scoring system that includes many parameters can be very useful for many surgeons to be able to assess the presence of gallbladder stones. Methods. The study was an analytic observational study with a cross sectional study design carried out in the digestive surgery polyclinic and the inpatient installation of Dr. Moh Husein general hospital, Palembang from September 2018 to May 2019. The sample of this study was all patients suspected of having gallbladder stones that met the inclusion and exclusion criteria. Results: Receiver operating characteristic (ROC) analysis of scoring on bile duct stone diagnosis had a cut-off of> 4 with a sensitivity value of 100% and a specificity of 75%. In the Fisher's Exact analysis test and it was found that the scoring had a significant relationship to the diagnosis of bile duct stones with an odd ratio (OR) value of 12.52. Conclusion. The use of a scoring system can predict the incidence of gallbladder stones.